A boosted decision tree approach using Bayesian hyper-parameter optimization for credit scoring. (15th July 2017) - Xia, Yufei; Liu, Chuanzhe; Li, YuYing; Liu, Nana
Highlights: A novel boosted tree model for credit scoring is proposed. A hyper-parameter optimization technique is developed based on TPE algorithm. The model is proved to outperform several baseline techniques. The model is validated on five datasets over five performance metrics. The feature importance scores and decision chart enhance model interpretation. Abstract: Credit scoring is an effective tool for banks to properly guide decision profitably on granting loans. Ensemble methods, which according to their structures can be divided into parallel and sequential ensembles, have been recently developed in the credit scoring domain. These methods have proven their superiority in discriminating borrowers accurately. However, among the ensemble models, little consideration has been provided to the following: (1) highlighting the hyper-parameter tuning of base learner despite being critical to well-performed ensemble models; (2) building sequential models (i.e., boosting, as most have focused on developing the same or different algorithms in parallel); and (3) focusing on the comprehensibility of models. This paper aims to propose a sequential ensemble credit scoring model based on a variant of gradient boosting machine (i.e., extreme gradient boosting (XGBoost)). The model mainly comprises three steps. First, data pre-processing is employed to scale the data and handle missing values. Second, a model-based feature selection system based on the relative feature importance scores is utilized to remove redundant variables. Third, the hyper-parameters of XGBoost are adaptively tuned with Bayesian hyper-parameter optimization and used to train the model with selected feature subset. Several hyper-parameter optimization methods and baseline classifiers are considered as reference points in the experiment. Results demonstrate that Bayesian hyper-parameter optimization performs better than random search, grid search, and manual search. Moreover, the proposed model outperforms baseline models on average over four evaluation measures: accuracy, error rate, the area under the curve (AUC) H measure (AUC-H measure), and Brier score. The proposed model also provides feature importance scores and decision chart, which enhance the interpretability of credit scoring model.